1947
DOI: 10.1097/00006254-194708000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Breast Abscesses With Penicillin

Abstract: The following account deals with various methods of treating breast abscesses with penicillin. The justification of those methods depended on their results as compared with those obtained from the methods at present employed. For this reason a series of controls was treated contemporaneously with Table Comtiparing Results in Breast Abscesses Duration in Days after First Treatment of No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The cost effectiveness ratio of Ultrasound guided aspiration was found to be much less than that of Incision and Drainage, thus indicating that Ultrasound guided aspiration provides savings to the hospital and the patient, hence more cost effective than Incision and Drainage. This was consistence with what was found elsewhere [ 11 , 13 ]. Since Ultrasound guided aspiration is an outpatient procedure as opposed to the Incision and Drainage which is inpatient procedure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The cost effectiveness ratio of Ultrasound guided aspiration was found to be much less than that of Incision and Drainage, thus indicating that Ultrasound guided aspiration provides savings to the hospital and the patient, hence more cost effective than Incision and Drainage. This was consistence with what was found elsewhere [ 11 , 13 ]. Since Ultrasound guided aspiration is an outpatient procedure as opposed to the Incision and Drainage which is inpatient procedure.…”
Section: Discussionsupporting
confidence: 93%
“…This was consistence with what was found elsewhere [11,13]. Since Ultrasound guided aspiration is an outpatient procedure as opposed to the Incision and Drainage which is inpatient procedure.…”
Section: Discussionsupporting
confidence: 89%
“…[13] and needle aspirations followed by antibiotics instillation. [14,15] In the present study in 100 patients, the mean age was 28.11 years. Two studies have reported mean age of approximately 32 years.…”
Section: Discussionmentioning
confidence: 72%
“…To our knowledge, there is only one old report considering the possibility of directly injecting antibiotics in the ABA: in 1946, Florey and co‐workers successfully treated 10 large ABAs by daily aspiration and local injection of a large amount of penicillin (11).…”
Section: Discussionmentioning
confidence: 99%